2021
DOI: 10.1016/j.jhep.2021.02.031
|View full text |Cite
|
Sign up to set email alerts
|

Freiburg index of post-TIPS survival (FIPS) a valid prognostic score in patients with cirrhosis but also an advisor against TIPS?

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 5 publications
1
13
0
Order By: Relevance
“…However, although patient numbers were small after sufficient propensity score matching, the authors showed that in the FIPS low-risk group, patients with TIPS implantation had significantly better overall survival compared to patients treated with paracenteses. 2 Indeed, as suggested by the authors, this observation may further underline the rationale that TIPS implantation should not be delayed in patients with ascites. To further address this interesting aspect, we analyzed 296 patients who received TIPS implantation for refractory ascites at the University Medical Center Freiburg (baseline characteristics: Table S3) and in whom the time between first ascitic decompensation and TIPS implantation was recorded.…”
mentioning
confidence: 61%
See 2 more Smart Citations
“…However, although patient numbers were small after sufficient propensity score matching, the authors showed that in the FIPS low-risk group, patients with TIPS implantation had significantly better overall survival compared to patients treated with paracenteses. 2 Indeed, as suggested by the authors, this observation may further underline the rationale that TIPS implantation should not be delayed in patients with ascites. To further address this interesting aspect, we analyzed 296 patients who received TIPS implantation for refractory ascites at the University Medical Center Freiburg (baseline characteristics: Table S3) and in whom the time between first ascitic decompensation and TIPS implantation was recorded.…”
mentioning
confidence: 61%
“…To the Editor: We thank Dr. Stockhoff and her team for their interest in our study 1 and their analyses that confirmed the prognostic impact of the Freiburg index of post-TIPS survival (FIPS) score and even expanded it to patients with decompensated cirrhosis without transjugular intrahepatic portosystemic shunt (TIPS) implantation. 2 With great interest, we recognize their efforts in addressing some important remaining questions from our study, especially with respect to the clinical application of the FIPS score for allocation to TIPS implantation. The authors point out several important issues which, however, require further attention.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, our results have been reproduced in 2 other independent cohorts of patients receiving TIPS. 2,6 Massoumy et al 6 and Wang et al 2 discussed if a modification of the cut-off for defining high-risk patients is necessary. Indeed, further validation of the FIPS score is necessary and these analyses should also focus on the determination of an optimal cut-off for selection of high-risk patients.…”
mentioning
confidence: 99%
“…In summary, as shown by several independent groups, the FIPS score is a reliable tool for identifying high risk patients with decompensated cirrhosis. [3][4][5] Further, it will be important to analyze if the FIPS score could be useful in decision-making, not only in the TIPS setting, but also in patients allocated for LT.…”
mentioning
confidence: 99%